The Role of the Election Organizer Honorary Council in Building Public Trust in Elections - Arizona, Vransiska Fami (Universitas Muhammadiyah Gorontalo, 2024)
The purpose of this study is to analyze and describe the role of the Election Organizer Honorary Council in the process of taking action against organizers who are considered to have violated the code of ethics in carrying out their duties. The method used in this study is Qualitative with content analysis of secondary data including verdict reports, current news on violations of the code of ethics, and relevant academic literature. The results of this study indicate that the firm action of the Election Organizer Honorary Council in handling violations of the code of ethics such as the imposition of administrative sanctions to dismissal still has a significant impact on increasing public trust in the organizers of the General Election. On the other hand, the results of this study also show that there are still limited resources, political pressure and low public understanding of the importance of the code of ethics are factors that cause high ethical violations committed by organizers. Therefore, this study emphasizes the importance of training for election organizers, strengthening election regulations, and socialization of the code of ethics to the community as a strategic step in resolving the problem of violations of the code of ethics of election organizers. Because if this can be realized, it is indirectly part of an effort to increase public trust in the organizers of the General Election.